PENGARUH KOMPETENSI APARATUR DESA, SISTEM PENGENDALIAN INTERNAL DAN KOMITMEN ORGANISASI TERHADAP AKUNTABILITAS PENGELOLAAN DANA DESA DI KECAMATAN MUARA ENIM KABUPATEN MUARA ENIM - Zulkifl Zulkifl; Sandrayati Sandrayati; Neni Ariani (JEMBATAN (Jurnal Ekonomi, Manajemen, Bisnis, Auditing, dan Akuntansi), 2021)
The purpose of this research is to determine the influence of village apparatus competency, internal control system, and organizational commitment to accountability of village fund management in Muara Enim Subdistrict, Muara Enim Subdistrict. The population in this study is village apparatus in ten villages in Muara Enim Subdistrict which is 70 people. With purposive sampling techniques, this study sampled as many as 40 respondents. The data is collected by distributing questionnaires directly to respondents. The data analysis technique used is multiple linear regression with SPSS version 25 software. The results showed the competence of village apparatus, internal control system and organizational commitment together have a positive and significant effect on the effectiveness of village fund management in Muara Enim Subdistrict, Muara Enim Regency. In part, the competence of village apparatus has a positive and significant effect on the accountability of village fund management. The control system has a positive and significant effect on the accountability of village fund management. The organization's commitment has a positive and significant impact on the accountability of village fund management.